Pengaruh Kemandirian Belajar terhadap Hasil Belajar Siswa Kelas X SMK - Setyanto; Rahmat Zulfan Fauzi; Ibrahim (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
One of the benchmarks in determining the level of student success in knowing and understanding a lesson is learning outcomes. Each student has different characteristics and enthusiasm for learning. Someone with independent learning takes the initiative and does not depend on others to solve the problems they face. This study intends to examine the effect of independent learning on students' mathematics learning outcomes in class XI SMK students. The research was conducted using a survey method in one of the private vocational schools in Sleman Regency. This study examines the relationship between student learning independence and student learning outcomes. After testing the hypothesis, it shows that there is an influence between students' learning independence on students' mathematics learning outcomes. The magnitude of the influence of student independence on student learning outcomes is 74% and 26% is influenced by other variables.